Targeting interleukin‐1 for reversing fat browning and muscle wasting in infantile nephropathic cystinosis. Issue 5 (30th June 2021) - Cheung, Wai W.; Hao, Sheng; Zheng, Ronghao; Wang, Zhen; Gonzalez, Alex; Zhou, Ping; Hoffman, Hal M.; Mak, Robert H.
Abstract: Background: Ctns −/− mice, a mouse model of infantile nephropathic cystinosis, exhibit hypermetabolism with adipose tissue browning and profound muscle wasting. Inflammatory cytokines such as interleukin (IL)‐1 trigger inflammatory cascades and may be an important cause for cachexia. We employed genetic and pharmacological approaches to investigate the effects of IL‐1 blockade in Ctns −/− mice. Methods: We generated Ctns −/− Il1β −/− mice, and we treated Ctns −/− and wild‐type control mice with IL‐1 receptor antagonist, anakinra (2.5 mg/kg/day, IP) or saline as vehicle for 6 weeks. In each of these mouse lines, we characterized the cachexia phenotype consisting of anorexia, loss of weight, fat mass and lean mass, elevation of metabolic rate, and reduced in vivo muscle function (rotarod activity and grip strength). We quantitated energy homeostasis by measuring the protein content of uncoupling proteins (UCPs) and adenosine triphosphate in adipose tissue and skeletal muscle. We measured skeletal muscle fiber area and intramuscular fatty infiltration. We also studied expression of molecules regulating adipose tissue browning and muscle mass metabolism. Finally, we evaluated the impact of anakinra on the muscle transcriptome in Ctns −/− mice. Results: Skeletal muscle expression of IL‐1β was significantly elevated in Ctns −/− mice relative to wild‐type control mice. Cachexia was completely normalized in Ctns −/− Il1β −/− mice relative to Ctns −/− mice. We showed that anakinra attenuated the cachexia phenotype in Ctns −/− mice. Anakinra normalized UCPs and adenosine triphosphate content of adipose tissue and muscle in Ctns −/− mice. Anakinra attenuated aberrant expression of beige adipose cell biomarkers (UCP‐1, CD137, Tmem26, and Tbx1) and molecules implicated in adipocyte tissue browning (Cox2/Pgf2α, Tlr2, Myd88, and Traf6) in inguinal white adipose tissue in Ctns −/− mice. Moreover, anakinra normalized gastrocnemius weight and fiber size and attenuated muscle fat infiltration in Ctns −/− mice. This was accompanied by correction of the increased muscle wasting signalling pathways (increased protein content of ERK1/2, JNK, p38 MAPK, and nuclear factor‐κB p65 and mRNA expression of Atrogin‐1 and Myostatin) and the decreased myogenesis process (decreased mRNA expression of MyoD and Myogenin) in the gastrocnemius muscle of Ctns −/− mice. Previously, we identified the top 20 differentially expressed skeletal muscle genes in Ctns −/− mice by RNAseq. Aberrant expression of these 20 genes have been implicated in muscle wasting, increased energy expenditure, and lipolysis. We showed that anakinra attenuated 12 of those top 20 differentially expressed muscle genes in Ctns −/− mice. Conclusions: Anakinra may provide a targeted novel therapy for patients with infantile nephropathic cystinosis.